2017
DOI: 10.5385/nm.2017.24.2.88
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Partial Short Arm Deletion in Chromosome 9 with Inguinal Hernia, Testicular Cystic Lesion, and Arthrogryposis Multiplex Congenita

Abstract: Chromosome 9p syndrome is a rare chromosomal abnormality caused by a partial deletion in chromosome 9. It was first described in 1973 by Alfi et al., and has since been shown to have diverse clinical phenotypes. Here, we reported a case of a male infant with joint contracture of the extremities, dysmorphic face, inguinal hernia, and testicular cystic masses. Chromosomal analysis revealed a terminal deletion at the short arm of chromosome 9. The major clinical features of the 9p deletion syndrome are trigonocep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Coarctation of the aorta is a rare manifestation of 9p deletion syndrome, which was reported by Koslow et al (2018) and observed in our patient 8. Other rare manifestations may be associated with 9p deletion syndrome like neonatal hyperinsulinemia/hypoglycemia (Bayata et al, 2018) and arthrogryposis multiplex congenita (Kim et al, 2017). Some authors have reported patients with 9p deletion associated with other chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Coarctation of the aorta is a rare manifestation of 9p deletion syndrome, which was reported by Koslow et al (2018) and observed in our patient 8. Other rare manifestations may be associated with 9p deletion syndrome like neonatal hyperinsulinemia/hypoglycemia (Bayata et al, 2018) and arthrogryposis multiplex congenita (Kim et al, 2017). Some authors have reported patients with 9p deletion associated with other chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%